Influence of Media Credibility and Information Quality on Visiting Interest: An Analysis of the @WonderfulIndonesia Instagram Account on Millennial Travelers - Purwitasari, Endah; Farida, Nuke; Wijaya, Widiastiana Vista; Wulandari, Christiana (Universitas Ahmad Dahlan, 2024)
Tourism in Indonesia holds significant potential, with domestic tourism being a primary focus for the government. The Ministry of Tourism and Creative Economy of the Republic of Indonesia has developed the